1993
DOI: 10.1126/science.8421785
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm in Membrane Conductance Expressed in Isolated Neurons

Abstract: Although isolated neurons can generate rhythmic activity, they have not yet been shown to generate rhythms with a period in the circadian range (near 24 hours). The eye of the mollusk Bulla gouldiana expresses a circadian rhythm in optic nerve impulses that is generated by electrically coupled cells known as basal retinal neurons (BRNs). Daily fluctuations in the membrane potential of the BRNs appear to be driven by a rhythm in membrane conductance. Isolated BRNs exhibited spontaneous conductance changes simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(109 citation statements)
references
References 17 publications
(9 reference statements)
4
104
0
Order By: Relevance
“…Discussion SCN Neurons Are Weak, Inducible, and Probabilistic Oscillators. The best examples to date of cell-autonomous circadian rhythm generation are unicellular cyanobacteria (21), dinoflagellates (22), and molluscan retinal neurons (23). Here we have demonstrated that when a single SCN neuron expresses PER2 for multiple days, it is likely to be circadian and can contain AVP, VIP, or another unidentified marker.…”
Section: Per2 Accumulation Predicts Oscillatory Abilitymentioning
confidence: 88%
“…Discussion SCN Neurons Are Weak, Inducible, and Probabilistic Oscillators. The best examples to date of cell-autonomous circadian rhythm generation are unicellular cyanobacteria (21), dinoflagellates (22), and molluscan retinal neurons (23). Here we have demonstrated that when a single SCN neuron expresses PER2 for multiple days, it is likely to be circadian and can contain AVP, VIP, or another unidentified marker.…”
Section: Per2 Accumulation Predicts Oscillatory Abilitymentioning
confidence: 88%
“…A crucial question early on in the field was whether or not cell-autonomous circadian oscillators also exist in multicellular organisms. The first demonstration of cell-autonomous circadian-rhythm generation in such organisms came from studies in the snail Bulla gouldiana, in which individual neurons in the base of the retina were shown to express circadian rhythms in membrane conductance for at least two days in culture 11 . In other landmark experiments in mammals, Welsh et al 12 established that the oscillatory machinery in rats functions within individual cultured SUPRACHIASMATIC NUCLEUS (SCN) neurons (discussed in detail later).…”
Section: Cell-autonomous Oscillatory Mechanismsmentioning
confidence: 99%
“…Another conserved feature of circadian mechanisms is that they are cell-autonomous; single cells dissociated in vitro can keep track of time even in complex multicellular animals (Michel et al 1993;Welsh et al 1995), although in vivo such cells are usually grouped into so-called timing centres.…”
Section: The Molecular Components Of Circadian Clocksmentioning
confidence: 99%